Studying the relationship between foreign donors and NGOs in developing countries: An effective or volatile partnership? - Gawish, Rana (AUC Knowledge Fountain, 2016)
The NGO-donor relationship is exceptionally volatile. NGOs, particularly in developing countries, rely heavily on donor funding. Resource dependence has directed NGOs to adjust their objectives to fit with donor priorities. Fluctuating preferences of donors lead NGOs to shift their behavior and respond to the objectives of the donor rather than the beneficiaries of the local community. Many NGOs in developing countries modify their activities and target groups to attain or sustain financial resources. One major consequence of this is that NGOs’ behavioral shift may have disconnected them from their constituents. Hence, aid allocated to recipient NGOs in developing countries may not be efficient in generating development in local communities. It is important to note that this research is not an evaluation of whether NGOs are ‘good’ or ‘bad’. The study is about the relationship between NGOs and donor agencies.